Channel Hopping Using p -ary m-Sequence for Rendezvous in Cognitive Radio Networks - Paul, Rajib; Choi, Young June; Jang, Jiwoong; Kim, Young Sik (IEEE Wireless Communications Letters, 2019)
Rendezvous is a process that assists nodes in a cognitive radio networks (CRNs) to discover each other. In CRNs where a common control channel is unknown and a number of channels are given, it is important how two nodes find each other in a known search region. In this letter, we have analyzed a channel hopping sequence considering {p} -ray m-sequence by which each node visits an available number of channels. We analyze the maximum and expected time-to-rendezvous (TTR) mathematically. The proposed sequence performs significantly better compared to the existing ones in term of maximum and expected TTR.
Keywords: Channel hopping; Cognitive radio network; Cognitive radio networks (CRNs); Common control channels; Expected time; Hopping sequences; P ary m sequences; rendezvous; Cognitive radio networks; hopping sequence; rendezvous; TTR